2018
DOI: 10.1007/s00023-018-0661-y
|View full text |Cite
|
Sign up to set email alerts
|

Self-Adjointness of Dirac Operators with Infinite Mass Boundary Conditions in Sectors

Abstract: This paper deals with the study of the two-dimensional Dirac operator with infinite mass boundary conditions in sectors. We investigate the question of self-adjointness depending on the aperture of the sector: when the sector is convex it is self-adjoint on a usual Sobolev space whereas when the sector is non-convex it has a family of self-adjoint extensions parametrized by a complex number of the unit circle. As a byproduct of the analysis we are able to give self-adjointness results on polygonal domains. We … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Many considerations in [ 22 , 23 , 61 ] are based on complex analysis techniques, which are not available in the 3D situation. We also refer to [ 28 , 47 , 48 , 57 ] for self-adjointness and spectral problems of 2D Dirac operators on different types of domains with special boundary conditions. In contrast to the 2D setting, was not directly investigated for general boundary parameters in 3D, as far as we know only the particular MIT bag operator is well studied.…”
Section: Introductionmentioning
confidence: 99%
“…Many considerations in [ 22 , 23 , 61 ] are based on complex analysis techniques, which are not available in the 3D situation. We also refer to [ 28 , 47 , 48 , 57 ] for self-adjointness and spectral problems of 2D Dirac operators on different types of domains with special boundary conditions. In contrast to the 2D setting, was not directly investigated for general boundary parameters in 3D, as far as we know only the particular MIT bag operator is well studied.…”
Section: Introductionmentioning
confidence: 99%
“…Eventually, in [27], a detailed study of the spectral properties of A 0,τ for purely scalar potentials was provided; in particular, it was shown that the discrete eigenvalues in the large mass limit are characterized by an effective operator on the surface . Furthermore, there is a great interest recently in the study of self-adjoint Dirac operators on domains with boundary conditions, see, e.g., [2,3,10,11,25,30,31,35,38].…”
mentioning
confidence: 99%
“…We follow the same strategy as in the proof of Lemma 3.2. By Proposition 3.4 and (19) we have, for ε −1 1 + c,…”
Section: Resolvent Estimatesmentioning
confidence: 75%
“…For further recent study of H Ω from the mathematical point of view see e.g. [7,19,10]. Note that in dimension 3, this infinite mass limit is strongly related to the MIT bag model for quarks confinement.…”
Section: Setting and Main Resultmentioning
confidence: 95%